Uji Antidiare Ekstrak Etanol Daun Matoa (Pometia pinnata) Terhadap Mencit Jantan Diinduksi Oleum Ricini - Fenny Hasanah; Muharni Saputri; Desi Natalia Siahaan; Putri Arya Kusuma; Sri Rezki Rudhoh Matondang (Journal of Pharmaceutical and Health Research, 2023)
Matoa leaf is a plant that is used as traditional medicine. Matoa leaves contain tannins, alkaloids, flavonoids, steroids, and glycosideswhich acts as an antidiarrheal. Oleum riciniis a triglyceride that is efficacious as a laxative. The purpose of this study was to prove that matoa leaves can be efficacious as an antidiarrheal. This study used an experimental method, using matoa leaf assay (Pometia pinnata J. R Forst & G. Forst.) with oleum ricini induction. This research includes the collection, processing, phytochemical screening, preparation of suspension of ethanol extract of matoa leaves, and testing the effectiveness antidiarrheal of suspension of ethanolic extract of matoa leaves (Pometia pinnata J.R. Forst& G. Forst.). The results of phytochemical screening on matoa leaf simplicia powder (Pometia pinnata J. R. Forst& G. Forst.) and ethanol extract of matoa leaf (Pometia pinnata J. R. Forst & G. Forst.) which has tannins, alkaloids, saponins, flavonoids, and triterpenoids. The results showed that EEDM at a dose of 300 mg/kg bw had an antidiarrheal effect comparable to EEDM at a dose of 150 mg/kg bw and had a stronger antidiarrheal effect than EEDM 75 mg/kg bw. The results also showed that the EEDM dose of 300 mg/kgbw was not significantly different from that of Loperamide HCl.